Time course of haemoglobin mass during 21 days live high:train low simulated altitude - Clark, S. A.; Quod, M. J.; Clark, M. A.; Martin, D. T.; Saunders, P. U.; Gore, C. J. (European Journal of Applied Physiology, 2009)
The aim of this study was to determine the time course of changes in haemoglobin mass (Hbmass) in well-trained cyclists in response to live high:train low (LHTL). Twelve well-trained male cyclists participated in a 3-week LHTL protocol comprising 3,000 m simulated altitude for ~14 h/day. Prior to LHTL duplicate baseline measurements were made of Hbmass, maximal oxygen consumption (VO2max) and serum erythropoietin (sEPO). Hbmass was measured weekly during LHTL and twice in the week thereafter. There was a 3.3% increase in Hbmass and no change in VO2max after LHTL. The mean Hbmass increased at a rate of ~1% per week and this was maintained in the week after cessation of LHTL. The sEPO concentration peaked after two nights of LHTL but there was only a trivial correlation (r = 0.04, P = 0.89) between the increase in sEPO and the increase in Hbmass. Athletes seeking to gain erythropoietic benefits from moderate altitude need to spend >12 h/day in hypoxia.